2019
DOI: 10.5433/1679-0359.2019v40n5p1775
|View full text |Cite
|
Sign up to set email alerts
|

Coleopterans prospection associated to forest ecosystems of Swietenia macrophylla (King), Eastern Amazonia

Abstract: Few research on the entomofauna associated to forest plantations with Swietenia macrophylla (King) in Brazil has been reported. The aim of this study was to analyze the Coleoptera communities in forest ecosystems with S. macrophylla, Brazilian mahogany, with emphasis on the diversity of families and the main functional groups. The insects were collected through pitfall traps in three forest ecosystems: monoculture, consortium and forest enriched with Brazilian mahogany, during dry and rainy periods in two cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Generally, this pattern is strongly linked to the presence of a vector, which transmits the disease over short distances, preferably within the planting line (Bassanezi & Laranjeira, 2007). This pattern is also observed by other authors who have studied the behavior of agricultural pests and who have shown that vector-infected plants have an effect on neighboring plants (Correia et al, 2019;Oliveira et al, 2016).…”
Section: Spatial Dependencesupporting
confidence: 61%
“…Generally, this pattern is strongly linked to the presence of a vector, which transmits the disease over short distances, preferably within the planting line (Bassanezi & Laranjeira, 2007). This pattern is also observed by other authors who have studied the behavior of agricultural pests and who have shown that vector-infected plants have an effect on neighboring plants (Correia et al, 2019;Oliveira et al, 2016).…”
Section: Spatial Dependencesupporting
confidence: 61%